Iatrogenic Duodenal Obstruction due to Acupuncture Therapy Trauma - Jae Hun Chung; Si-Hak Lee (Journal of Trauma and Injury)
There are many possible causes of duodenal obstruction, such as congenital anomalies and various acquired conditions associated with space-occupying lesions. However, hemorrhage or retroperitoneal hematoma is a rare cause of duodenal obstruction. Here, we report the case of a 55-year-old man who developed duodenal obstruction due to a large retroperitoneal hematoma after acupuncture therapy. The patient experienced abdominal discomfort along with vomiting and nausea. Considering the size of the hematoma, emergency surgery could have been performed, but conservative treatment was continued because the patient’s vital signs were stable. With spontaneous resolution of the hematoma, the symptoms of duodenal obstruction improved. The patient was eventually discharged without any complications associated with the hematoma. Our findings suggest that even when a hematoma is large, a conservative approach can be maintained until improvement of the symptoms of duodenal obstruction if the vital signs of the patient remain stable.